Metagenomic Insights for Antimicrobial Resistance Surveillance in Soils with Different Land Uses in Brazil - João Vitor Wagner Ordine; Gabrielle Messias de Souza; Gustavo Tamasco; Stela Virgilio; Ana Flávia Tonelli Fernandes; Rafael Silva-Rocha; María-Eugenia Guazzaroni (MDPI AG, 2023)
Land-use conversion changes soil properties and their microbial communities, which, combined with the overuse of antibiotics in human and animal health, promotes the expansion of the soil resistome. In this context, we aimed to profile the resistome and the microbiota of soils under different land practices. We collected eight soil samples from different locations in the countryside of São Paulo (Brazil), assessed the community profiles based on 16S rRNA sequencing, and analyzed the soil metagenomes based on shotgun sequencing. We found differences in the communities' structures and their dynamics that were correlated with land practices, such as the dominance of Staphylococcus and Bacillus genera in agriculture fields. Additionally, we surveyed the abundance and diversity of antibiotic resistance genes (ARGs) and virulence factors (VFs) across studied soils, observing a higher presence and homogeneity of the vanRO gene in livestock soils. Moreover, three β-lactamases were identified in orchard and urban square soils. Together, our findings reinforce the importance and urgency of AMR surveillance in the environment, especially in soils undergoing deep land-use transformations, providing an initial exploration under the One Health approach of environmental levels of resistance and profiling soil communities.